2004
DOI: 10.1075/tsl.62.10wal
|View full text |Cite
|
Sign up to set email alerts
|

On some interactional and phonetic properties of increments to turns in talk-in-interaction

Abstract: This report is based on phonetic and interactional analysis of a collection of increments drawn from audio recordings of British and North American talk-in-interaction. An increment is a grammatically fitted continuation of a turn at talk following the reaching of a point of possible syntactic, pragmatic, and prosodic completion. Parametric phonetic analysis reveals that a range of phonetic parameters (including pitch, loudness, rate of articulation, and articulatory characteristics) mark out an increment as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(28 citation statements)
references
References 6 publications
1
24
0
3
Order By: Relevance
“…17 The practice of completing a turn in a delayed fashion after an intervening response thus typically occurs in argumentative talk, even in disagreements. It is interesting that both Schegloff (2001) and Walker (2004) have found that regarding different types of increments -continuations of already completed turns -, it is the ones positioned after a gap that orient to 17 A phenomenon related to the one examined here is that of collaborative completions (see Lerner 1996, 2004b, also Vatanen 2014: 151ff. and, e.g., Kim 1999.…”
Section: Summary and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 The practice of completing a turn in a delayed fashion after an intervening response thus typically occurs in argumentative talk, even in disagreements. It is interesting that both Schegloff (2001) and Walker (2004) have found that regarding different types of increments -continuations of already completed turns -, it is the ones positioned after a gap that orient to 17 A phenomenon related to the one examined here is that of collaborative completions (see Lerner 1996, 2004b, also Vatanen 2014: 151ff. and, e.g., Kim 1999.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Hence, the ajattele in line 12 seems to be pivotal (see Linell 1981;Walker 2004) in that it can belong to both the preceding and the following talk, forming a multi-unit turn with one and/or the other. Retrospectively, it combines all the three TCUs into one multi-unit turn.…”
Section: C: N(h)ii;mentioning
confidence: 99%
“…The function of revising the question is to change the way it is formulated with a view to an aligning response (Schegloff 2007). After the delay, the therapist changes his question by adding an increment to it-a unit of talk that is grammatically fitted to a turn that has already been brought to possible completion (Walker 2004). The extension of the question to refer to vacuuming recycles something of the previously told anecdote with a twist because vacuuming would likely be housework that the wife did anyway.…”
Section: Responsive Laughter To Build Rapportmentioning
confidence: 99%
“…This interpretation is underlined by the very low intonation on the increment in line 3 in Example (11), and its fast production. It recompletes the unit that was potentially already complete with falling intonation on khum, and the increment is therefore produced even lower, which is one possible prosodic characteristic of increments (as discussed by Walker, 2004).…”
Section: Other-and Postcompletionmentioning
confidence: 99%